2022
DOI: 10.15857/ksep.2022.00297
|View full text |Cite
|
Sign up to set email alerts
|

Association between Light Intensity Physical Activity and All-cause Mortality in Older Adults with Physical Disability

Abstract: PURPOSE: This study aimed to investigate the association between light intensity physical activity (LPA) and all-cause mortality in older adults with physical disability.METHODS: Data from the 2008 Living Profiles of Older People Survey involving 14,367 Korean adults aged ≥60 years (13,417 without disabilities and 950 with disabilities) were used. Participants were divided into active and inactive groups based on weekly LPA and moderate-to-vigorous intensity physical activity (MVPA). Cox proportional hazards r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Physical disabilities are acquired, and they are the most common type among older adults. A previous study reported that the prevalence of physical disabilities in the elderly population aged ≥65 years was 9.51%, higher than 2.55% in the total sample [45]. In addition, a study found that older adults living in the metropolitan area accounted for 15.4% and those living in non-metropolitan areas accounted for 19.5% of the total population [46].…”
Section: Discussionmentioning
confidence: 99%
“…Physical disabilities are acquired, and they are the most common type among older adults. A previous study reported that the prevalence of physical disabilities in the elderly population aged ≥65 years was 9.51%, higher than 2.55% in the total sample [45]. In addition, a study found that older adults living in the metropolitan area accounted for 15.4% and those living in non-metropolitan areas accounted for 19.5% of the total population [46].…”
Section: Discussionmentioning
confidence: 99%